12.01: Global plastic design of stainless steel frames. (13th September 2017) - Arrayago, Itsaso; Real, Esther; Mirambell, Enrique; Chacón, Rolando
ABSTRACT: The use of stainless steel structures has increased during the last decade due to their durability, aesthetics and mechanical properties such as ductility, considerable strain hardening and excellent fire resistance. However, the majority of conducted research works have only focused on single isolated stainless steel members and advances in the analysis of stainless steel frames are limited. EN1993‐1‐4 does not provide global plastic design rules for indeterminate stainless steel structures, such as frames, despite their proved high ductility. On the other hand, the lack of guidance on plastic design is an obstacle for the optimal design of stainless steel structures, leading to uneconomical design. This paper presents a preliminary study on non‐sway stainless steel frames with stocky hollow cross‐sections. The study of the behaviour of stainless steel frames is based on numerical parametric studies, considering the nonlinear material behaviour and different stainless steel types (austenitic and ferritic). The paper deals with the redistribution of internal forces and assesses the existing methods based on global plastic design for frames with stocky cross‐sections, where alternative design approaches accounting for moment redistribution and strain hardening effects are analysed in addition to traditional plastic design method. Preliminary results demonstrate that including bending moment redistribution and strain hardening effects in capacity predictions is essential for an efficient design of stainless steel structures.